2001
DOI: 10.1128/jb.183.2.443-450.2001
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of Eleven Different DNA Methyltransferases of Helicobacter pylori Strain 26695

Abstract: Methyltransferases (MTases) of procaryotes affect general cellular processes such as mismatch repair, regulation of transcription, replication, and transposition, and in some cases may be essential for viability. As components of restriction-modification systems, they contribute to bacterial genetic diversity. The genome of Helicobacter pylori strain 26695 contains 25 open reading frames encoding putative DNA MTases. To assess which MTase genes are active, strain 26695 genomic DNA was tested for cleavage by 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 50 publications
6
46
0
Order By: Relevance
“…These results indicated that HP itself was not necessary for methylation induction once inflammation was induced by it. This finding is important because a direct role of HP is suggested by the facts that the SHP2 oncoprotein is deregulated by injection of virulent factors such as CagA into GECs (34) and HP possesses multiple DNA (cytosine-5) methyltransferases (35).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that HP itself was not necessary for methylation induction once inflammation was induced by it. This finding is important because a direct role of HP is suggested by the facts that the SHP2 oncoprotein is deregulated by injection of virulent factors such as CagA into GECs (34) and HP possesses multiple DNA (cytosine-5) methyltransferases (35).…”
Section: Discussionmentioning
confidence: 99%
“…First, because H. pylori possesses multiple DNA methyltransferases (46) and a type IV secretion system [a syringe-like structure capable of delivering bacterial materials into a host cell (47) H. pylori infection Figure 1. Formation of epigenetic field for cancerization by chronic inflammation triggered by H. pylori infection.…”
Section: Critical Roles Of Specific Types Of Inflammation In Methylatmentioning
confidence: 99%
“…Helicobacter pylori, a gram-negative bacterium that colonizes the human stomach, affects the risk of getting upper gastrointestinal tract diseases, including gastric cancer (13). H. pylori strains are highly heterogeneous in terms of the number and nature of the R-M systems that they carry (2,10,11,18,19,21,23). During characterization of the hpyIIIR-hpyIIIM locus in Asian and Western strains, we found numerous strains with a novel gene that we designated hrgA in place of hpyIIIR (encoding an isoschizomer of Moraxella bovis MboI).…”
mentioning
confidence: 99%